2020
DOI: 10.5194/acp-20-6607-2020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Southern Ocean cloud in the HadGEM3 general circulation model and MERRA-2 reanalysis using ship-based observations

Abstract: Abstract. Southern Ocean (SO) shortwave (SW) radiation biases are a common problem in contemporary general circulation models (GCMs), with most models exhibiting a tendency to absorb too much incoming SW radiation. These biases have been attributed to deficiencies in the representation of clouds during the austral summer months, either due to cloud cover or cloud albedo being too low. The problem has been the focus of many studies, most of which utilised satellite datasets for model evaluation. We use multi-ye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 100 publications
4
30
0
Order By: Relevance
“…This result has significance for lidar-only or ceilometer datasets that are currently used for validation of climate models (e.g. Kuma et al, 2020). The occurrence of ice at these relatively warm temperatures is also in line with airborne in-situ observations over the Southern Ocean (Huang et al, 2017;D'Alessandro et al, 2019).…”
Section: Comparison Of Radar Reflectivity Factor Of the Ice Virgasupporting
confidence: 69%
See 1 more Smart Citation
“…This result has significance for lidar-only or ceilometer datasets that are currently used for validation of climate models (e.g. Kuma et al, 2020). The occurrence of ice at these relatively warm temperatures is also in line with airborne in-situ observations over the Southern Ocean (Huang et al, 2017;D'Alessandro et al, 2019).…”
Section: Comparison Of Radar Reflectivity Factor Of the Ice Virgasupporting
confidence: 69%
“…Young, 1999) and one of the cloudiest places on Earth (Haynes et al, 2011;Naud et al, 2014), but process understanding of clouds in that region is still limited. The reported biases in the solar radiation budget are attributed to shallow supercooled liquid topped clouds, which are insufficiently represented by current models (Bodas-Salcedo et al, 2014;Kay et al, 2016;Bodas-Salcedo et al, 2016;Kuma et al, 2020). These radiation biases affect estimates of sea surface temperature and surface precipitation, ultimately affecting the energy balance at the surface (Franklin et al, 2013;Hyder et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that there is currently a large shortwave radiation bias over the Southern Ocean (Bodas‐Salcedo et al, ). Observations of cloud base height from radiosondes and ceilometer measurements throughout this same voyage showed that the shortwave radiation bias is related to the lack of low‐level cloud and fog predicted within atmospheric models (Kuma et al, ). Therefore, it is reasonable to expect that even with an improved in‐cloud activation scheme (e.g., Grythe et al, ), FLEXPART‐WRF still would have underestimated the frequency of droplet activation events.…”
Section: Resultsmentioning
confidence: 99%
“…It is useful, however, to recall that clouds over the Southern Ocean are not very well represented within modern atmospheric models (Schuddeboom et al, ; Trenberth & Fasullo, ). Current era atmospheric models systematically underpredict the amount of low‐lying cloud and fog relative to the true cloud observed over the Southern Ocean (Kuma et al, ). Hence, even if a state‐of‐the‐art microphysical parameterization of in‐cloud scavenging had been present in FLEXPART‐WRF, it is likely that the scavenging of sea spray still would have been underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Second, sea-air temperature difference is also a key factor in sea fog formation (Koračin et al, 2014). In regions where the value of SST-T2M is near zero (the air temperature is slightly lower than the water temperature), fog formation could be more common (Koračin et al, 2014;Kuma et al, 2020). This process could scavenge SSA masses from the boundary layer and potentially explain the phenomenon observed (Figure 3b).…”
Section: Influence Of Sea-air Temperature Differences On the Spatial Distribution Of Ssamentioning
confidence: 98%